Effects of social media influencer attributes on consumers’ attitudes and purchase intention - Mohamed, El Mousa Hadeel Ali (2022)
Brands collaborate with social media influencers to promote their products through influencer marketing. Companies are increasingly depending on social media influencers to promote their brands owing to the potential of influencers in connecting the target audience with the company while maintaining a direct connection with their followers. However, research on influencer marketing is very sparse, particularly in Malaysia. As a result, the purpose of this study is to fill a gap in the literature and the industry by validating the effect of social media influencers on customer attitudes and intentions toward endorsement. An online questionnaire was distributed to the respondents. Three hundred fifty answers were obtained using the purposive sampling approach. All of the responders were Malaysians from various states. The hypotheses were tested using partial least squares (PLS), a variance-based Structural Equation Modelling (SEM) approach. In SEM-PLS, statistical analyses were performed and interpreted in two stages: measurement model assessment and structural model assessment. The findings confirmed the model by validating that source credibility, meaning transfer, and subjective norms were significantly associated with attitude. Also, source credibility, subjective norms, and attitude were significantly associated with purchase intention. Eventually, the attitude was found to strengthen the relationships between source credibility, meaning transfer, and subjective norms with purchase intention towards the endorsed products. In many respects, this study contributes to the marketing literature and industry. First, the Psychology field's Theory of Reasoned Action was utilized to illustrate ii the link between attitudes and behaviours inside human activities, which is currently being extended to an influencer marketing setting in Malaysia. Second, this study adds to the literature on influencer marketing by determining the effect of the variables source credibility, meaning transfer, and subjective norms on attitude and purchase intention in the setting of influencer marketing. Furthermore, one of the study's outcomes is the identification of a relatively new variable, subjective norms, to quantify the impact of social media influencers using the Theory of Reasoned Action. The results of this study can provide deep insights and guidelines for companies, marketers, marketing agencies, and influencers. Social media influencers cannot only appeal to a broad audience but also act as marketers efficiently. Endorsing products and brands is very beneficial, both for social media influencers themselves and the brands. Empirical proof of the purchase intention of products recommended by social media influencers is required for industry practitioners to make a strategic choice on whether or not to expand investment in influencer marketing. To conclude, influencer marketing is still new to the Malaysian market. However, it has proven its importance as it showed considerable success in affecting consumers' attitudes and intentions toward the endorsed products.